Low energy dart test for mechanical evaluation of ophthalmic materials - Martínez, Antonio B; Artús, Pau; Dürsteler, Juan C; Arencón, David (Optometry and vision science, 2009)
Many impact tests fail to rigorously analyze the polymer behavior at impact, because they are performed in an energy range too different from real-life incidents, use specimens with other geometries than those of their final application, or they do not take in account polymer viscoelastic nature. A novel low energy impact method that overcomes current method limitations is presented for ophthalmic polymers and advances our understanding of the behavior of these materials under impact conditions. Plate-shaped specimens of two known materials, CR-39 and Superfin, were tested in an energy range around their failure limit. A non-conservative model was proposed to predict the dynamic response of the specimens that did not fail. Both the deflection and indentation mechanisms were introduced in the model, which was solved using a fourth order Runge-Kutta numerical method. Damper coefficients that were introduced to model the energy dissipation and elastic modulus were obtained after the fitting process. Rupture stress and absorbed energy at failure were obtained from the specimens that failed. Very good agreement between experimental and calculated data was observed. Under non-failure conditions, Superfin and CR-39 showed similar elastic modulus, although slightly larger energy dissipation was observed for CR-39. However, Superfin clearly outperformed CR-39 when measuring rupture stress and absorbed energy at failure with values 54% and 170% larger, respectively. Low energy impact methods are a very powerful tool to study and compare ophthalmic materials. The model satisfactorily predicted the behavior of materials in low energy impact conditions and can be used to obtain critical material characteristics. In this particular case, the method was used to quantify mechanical differences among CR-39 and Superfin. Of these two, the latter is the best performing material.